Eavesdropping attack on a continuous-variable source-independent quantum random number generator with fluctuating local oscillator. (23rd March 2022) - Zhou, Han; Zheng, Ziyong; Huang, Luyu; Wang, Xiangyu; Chen, Ziyang; Yu, Song
Abstract: In the practical continuous-variable source-independent quantum random number generator, it is usually necessary to introduce a local oscillator to amplify the received quantum signal due to its weak intensity. However, the intensity fluctuation of the local oscillator itself will lead to a deviation in evaluating the randomness without monitoring the local oscillator in real time and calibrating each output measurement, which will inevitably open a loophole for the eavesdropper to intercept the information of generated random numbers. Here, we present an eavesdropping attack utilizing this loophole. The results of numerical simulation indicate that when the proposed eavesdropping attack is performed, the evaluated extractable randomness value will be compromised severely, which will impact the communication security under the practical conditions. Meanwhile, we analyze the effects of practical imperfections in the presence of local oscillator fluctuation. Taking this as a reference, we may consider how to perfect the experimental system in practice and how to deal with this kind of eavesdropping attack.